Analisis Budaya Pantangan Makanan terhadap Asupan Gizi Ibu Hamil: Literature Review - Fitriani, Amelia Salsabila; Kusumaningtiyas, Aprilia; Aulia, Fahrani Nur; Agustin, Fryda; Nurafni, Nurafni; Kismayarti, Syahda Rofila; Aditya, Ronal Surya (Universitas Negeri Malang, 2024)
Cultural and social norms surrounding food consumption during pregnancy can have a significant impact on pregnant women's intake. This literature review aims to analyze the cultural taboo on food consumption among pregnant women and its influence on nutritional intake. This review highlights various cultural beliefs and practices that influence food choices during pregnancy, including avoidance of certain foods due to cultural norms. This research also examines the impact of these restrictions on the nutritional status of pregnant women, including the potential risk of malnutrition on the health of the mother and fetus. These findings suggest that cultural taboos against food consumption can have a significant impact on the nutritional intake of pregnant women, in order to provide effective prenatal care and nutrition education. with research topics published in the last 10 years starting from 2014 to the latest. Use library sources from websites or national and international journal articles. The culture that lives in society has messages that it wants to convey, such as food restrictions for pregnant women which are believed to have been passed down from generation to generation and cause feelings of doubt and fear when consuming food because there is a fear that something will happen.